Primary headaches: analysis of comorbidities associated with tension-type headaches - Lopes, Thiago Luís Marques; Sousa, Arthur Vitor Couto de; Penha, Guilherme Matos da; Clarindo, José Fernando Muniz; Filho, Hildel Freire Leite; Ferreira, Eduarda Lima Verde (Headache Medicine, 2023)
Full abstract in PDF.